Lingkungan Keluarga Sebagai Klinik Budaya Literasi Untuk Menciptakan Reading Society Sejak Dini - Umi Masturoh; Firdausi Nuzula Apriliyana (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The family environment becomes a cultural literacy clinic, so that the habit of reading continues to be encouraged starting from the time the child is a member of the family. Families need to be able to support each other and optimize as best they can to design their family members to have an interest in reading without having to be ordered but as a lifestyle requirement in the family environment itself. For this reason, the family environment that is built must become a planned literacy culture clinic. The literacy culture clinic that is raised for each family member is needed to have a positive impact on children from an early age if the components involved can support each other and create harmony that builds a reading society. Literacy is an literacy, which is a set of individual skills in terms of reading, writing, speaking, arithmetic and solving simple problems of everyday life. Literacy culture is intended to carry out thinking habits followed by a process of reading, writing or other skills which in the end what children do in a process of these activities will create works. The family environment is a very important component in producing a society. The habits of a child formed by a family environment will greatly affect the macro culture of society related to literacy of society. The built family environment should have the principles of mobilizing and motivating, purposeful, experience oriented, recognition and reward, social transmission, and exemplary by parents. (parents provide examples). Just like being a clinic that facilitates a service related to literacy, it is necessary to prepare a home environment that can support the habit of literacy. The most important part to realize a literacy culture clinic at home is to prepare "adequate management of learning resources and adapted to the needs of each child's age". The conclusion is a cultural literacy clinic in the family environment. If it continues to function, then the benefits of the services that have been provided will be able to familiarize family members into families who like to read, improve communication between families, discussion will be a solution or a way out to solve problems, increase innovative and creative thinking and rich in information experience.